1998
DOI: 10.1002/j.1556-6978.1998.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

The Counselor Educator Crunch Revisited: A Status Report

Abstract: This article is the 3rd in a series of investigations into the supply and demand of qualified counselor educators for the oncoming millennium.As part of a continuing investigation, this article represents the most recent findings on the supply of and opportunities for counselor educators. The first study (Maples, 1989) and the second study (Maples, Altekruse, & Testa, 1993) collected data on counselor education vacancies from position announcements in the Chronicle of Higher Education and Counseling Today. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
2
9
0
Order By: Relevance
“…The present study indicates that the CE degree is clearly sought in the marketplace, specifically for faculty positions. It supports findings that have predicted strong employment possibilities for CEs (Maples et al, 1993;Maples & Macari, 1998;Rogers et al, 1998). On the other hand, the findings could raise concern in light of what Zimpfer (1996) reported to be the clinical interests of CEs.…”
Section: Conclusion and Directions For Researchsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study indicates that the CE degree is clearly sought in the marketplace, specifically for faculty positions. It supports findings that have predicted strong employment possibilities for CEs (Maples et al, 1993;Maples & Macari, 1998;Rogers et al, 1998). On the other hand, the findings could raise concern in light of what Zimpfer (1996) reported to be the clinical interests of CEs.…”
Section: Conclusion and Directions For Researchsupporting
confidence: 87%
“…The work of Maples and her colleagues (Maples, 1989;Maples, Altekruse, & Testa, 1993;Maples & Macari, 1998) established the need for an increased pool of counselor education graduates (CEs) in the foreseeable future to fill faculty positions in counselor education programs. These predictions were further supported by Rogers et al (1998) who reported that programs accredited by the Council for Accreditation of Counseling and Related Educational Programs (CACREP) projected a need for 211 new faculty members over 10 years.…”
mentioning
confidence: 99%
“…It is surprising, however, to note that even with evidence that over a 9-year period demand exceeded supply for counselor educators (Maples & Macari, 1998), a dearth of literature exists regarding doctoral students in counselor education programs (Boes, Ullery, Millner, & Cobia, 1999;Bruce, 1995). Despite the doctoral students' importance to the field of counseling, counselor education has placed little emphasis on studying their experience.…”
mentioning
confidence: 96%
“…Research has found the doctoral degree in counselor education to be vital and unrivaled, producing well-trained students who provide a variety of services in the human relations field (Lanning, 1990;Vacc, 1990;Wittmer & Loesch, 1990). It is surprising, however, to note that even with evidence that over a 9-year period demand exceeded supply for counselor educators (Maples & Macari, 1998), a dearth of literature exists regarding doctoral students in counselor education programs (Boes, Ullery, Millner, & Cobia, 1999;Bruce, 1995). Despite the doctoral students' importance to the field of counseling, counselor education has placed little emphasis on studying their experience.…”
mentioning
confidence: 99%
“…We present a profile of the new assistant professors and qualitative data that may contribute to more effective and efficient efforts to recruit candidates for faculty positions. Maples (1989) and Maples and Macari (1998) have conducted longitudinal studies addressing similar research questions; however. respondents for their studies have been department representatives.…”
mentioning
confidence: 99%